2017
DOI: 10.1007/s10339-017-0792-y
|View full text |Cite
|
Sign up to set email alerts
|

Attention to body-parts varies with visual preference and verb–effector associations

Abstract: Theories of embodied conceptual meaning suggest fundamental relations between others' actions, language, and our own actions and visual attention processes. Prior studies have found that when people view an image of a neutral body in a scene they first look toward, in order, the head, torso, hands, and legs. Other studies show associations between action verbs and the body-effectors used in performing the action (e.g., "jump" with feet/legs; "talk" with face/head). In the present experiment, the visual attenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Among them fronto-parietal circuit was evidenced to play predominant role (Rizzolatti et al 1997 ; Jeannerod 1999 ; Galati et al 2001 ; Mohr et al 2006 ; Tsakiris et al 2007 ; Kemmerer and Tranel 2008 ). Third, human body (faces and other body parts) gains a special status as socially relevant stimuli which play a privileged role in perceptual processing (Bracco and Chiorri 2009 ; Boyer et al 2017 ). As a result, body is a specific mental category within which data are processed faster comparing to other objects of a similar complexity (Shontz and McNish 1972 ; Ro et al 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among them fronto-parietal circuit was evidenced to play predominant role (Rizzolatti et al 1997 ; Jeannerod 1999 ; Galati et al 2001 ; Mohr et al 2006 ; Tsakiris et al 2007 ; Kemmerer and Tranel 2008 ). Third, human body (faces and other body parts) gains a special status as socially relevant stimuli which play a privileged role in perceptual processing (Bracco and Chiorri 2009 ; Boyer et al 2017 ). As a result, body is a specific mental category within which data are processed faster comparing to other objects of a similar complexity (Shontz and McNish 1972 ; Ro et al 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our findings indicate that hierarchical models of action perception may need to account for this varying reliance on form and motion information (Parisi et al, 2015). In the context of hierarchical models, our findings do suggest that kinematics of body-parts are a relevant step in the process of action recognition (Boyer et al, 2017;de C. Hamilton and Grafton, 2008), but only when those kinematics are directly present, as in the case of dynamic stimuli. Aside from these issues related to the presentation format of the images, there are other factors at stake that pertain to the semantics of the images.…”
Section: Neural Basis Of Visual Action Perceptionmentioning
confidence: 61%
“…Arms are in contact with mirror more than legs in daily life; mirrors reflect same-direction operations (e.g., when combing hair with our left hand, we will see a movement of combing hair on the left side of the mirror). In some laboratory studies, researchers have reported that when people look at an image of a neutral body (Kano & Tomonaga, 2009) or an actor pantomiming a movement (Boyer et al, 2017) in a scene, the arm (movements) receives more attention resources than the leg (movements). Therefore, it is easier for arms than for legs to associate with the same direction.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the mirrors we look at every day reflect same-direction operations, resulting in more occurrences of same-direction operation than opposite-direction operation. In addition, in a scene, legs and leg movements receive fewer attention resources than arms and arm movements (Boyer et al, 2017; Kano & Tomonaga, 2009). Compared with their legs, individuals are more accustomed to using their arms to perform movements (see Velloso et al, 2015).…”
Section: Discussionmentioning
confidence: 99%